Impact of three years continuous wastewater irrigations on the soil chemical properties under turfgrass (Cynodon dactylon) - GURJAR, D S; KAUR, R; LAL, KHAJANCHI; SINGH, R; SINGH, K P (The Indian Journal of Agricultural Sciences, 2020)
An investigation was carried out to assess short-term (2013–16) impact of wastewater irrigations on the chemical properties of the soil under turfgrass (Cynodon dactylon L. var. Selection-1), planted with and without sub-soil porous plastic mulch, in the experimental field of the Water Technology Centre of ICAR-IARI, New Delhi. The investigation comprised 3-replicates of 2 –groundwater irrigation scheduling treatments (each of 50 mm depth) at 100% ETc and 6- treatments of wastewater irrigation scheduling (also of 50 mm depth each) at 75%, 100% and 125% ETc, under with and without sub-soil porous plastic mulch planting. The investigation revealed a non-significant change in the rhizosphere soil pH and EC under all wastewater irrigation treatments. However, a significant (14 to 25%) increase in the soil organic carbon, particularly under the more frequently (i.e. at 75% ETc) wastewater irrigated plots, was observed. These were also found to be associated with increased soil major (N: 8.5 to 15.2%; P: 45.7 to 62.8%; K: 12 to 34.7%) and micro nutrients (Zn: 22.4 to 29.5%; Mn: 16.9 to 27.1 %; Cu: 21.9 to 19.2% and Fe: 15.6 to 24.8%). However, there was no heavy metal built-up in such wastewater irrigated soils probably due to their presence in within permissible levels in the applied irrigation waters. The investigations thus indicated a great potential of improved soil health, with no heavy metal threats, under short-term wastewater irrigation applications in urban turfgrass based landscapes.